The characterisation of overweight and obese women who are under reporting energy intake during pregnancy - L. J. Moran; S. A. McNaughton; Z. Sui; C. Cramp; A. R. Deussen; R. M. Grivell; J. M. Dodd (BMC, 2018)
Abstract Background Misreporting of energy intake is common and can contribute to biased estimates of the relationship between diet and disease. Energy intake misreporting is poorly understood in pregnancy and there is limited research assessing characteristics of women who misreport energy intake or changes in misreporting of energy intake across pregnancy. Methods An observational study in n = 945 overweight or obese pregnant women receiving standard antenatal care who participated in the LIMIT randomised trial. Diet, physical activity, psychological factors, body image satisfaction and dieting behaviour were assessed at trial entry (10-20 weeks gestation) and 36 weeks gestation. Energy misreporting status was assessed through the ratio of daily energy intake over basal metabolic rate. Logistic regression analyses were conducted with the dependent variable of under reporting of energy intake at study entry or 36 weeks in separate analysis. Results At study entry and 36 weeks, women were classified as under reporters (38 vs 49.4%), adequate reporters (59.7 vs 49.8%) or over reporters of energy intake (2.3 vs 0.8%) respectively. The prevalence of under reporting energy intake at 36 weeks was higher than at study entry (early pregnancy). Body mass index (BMI) at study entry and 36 weeks and socioeconomic status, dieting behaviour and risk of depression at 36 weeks were independent predictors of under reporting of energy intake. Conclusions Under reporting of energy intake was present in over a third of overweight and obese pregnant women and was higher in late compared to early pregnancy. Characteristics such as BMI, socioeconomic status, past dieting behaviour and risk of depression may aid in identifying women who either require support in accurate recording of food intake or attention for improving diet quality. Results were unable to distinguish whether under reporting reflects misreporting or a true restriction of dietary intake. Trial registration Australian and New Zealand Clinical Trials Registry ACTRN12607000161426, registered 9/3/2007.